Influence of short and prolonged maternal undernutrition on the twin ovine fetus and postnatal lamb - Field, Meghan Elizabeth, author; Han, Hyungchul, advisor; Anthony, Russ, advisor; Engle, Terry, committee member; Hansen, Thomas, committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: fetal growth; sheep; maternal undernutrition